Discovery and optimization of pyrazolopyrimidine sulfamates as ATG7 inhibitors - Huang, Shih-Chung; Adhikari, Sharmila; Brownell, James E.; Calderwood, Emily F.; Chouitar, Jouhara; D'Amore, Natalie Roy; England, Dylan B.; Foley, Klaudia; Harrison, Sean J.; LeRoy, Patrick J.; Lok, David; Lublinsky, Anna; et al. (Bioorganic & medicinal chemistry, 2020)
[Display omitted] Autophagy is postulated to be required by cancer cells to survive periods of metabolic and/or hypoxic stress. ATG7 is the E1 enzyme that is required for activation of Ubl conjugation pathways involved in autophagosome formation. This article describes the design and optimization of pyrazolopyrimidine sulfamate compounds as potent and selective inhibitors of ATG7. Cellular levels of the autophagy markers, LC3B and NBR1, are regulated following treatment with these compounds.